ANALISIS SISTEM PENCEGAHAN BAHAYA KEBAKARAN PADA GEDUNG MUSEUM PENERANGAN DI KAWASAN WISATA TAMAN MINI INDONESIA INDAH - Upara, Nafsan; Prinajati, PS.Dyah (Universitas Sahid, 2019)
Museum Penerangan is one of tourist attractions which is visited by tourist to increase the knowledge of lighting development in Indonesia. Museum Penerangan has fire protection system, but the reliability of building safety system of potential fire hazard needs to be known. This research is conducted to acknowledge Museum Penerangan reliability of building safety system. Reliability variables used in this research are the completeness of treads, safety tools, active fire protective systems, and passive fire protective systems. The research obtains the value of reliability of Museum Penerangan building safety system for potential fire hazard is 68,9895, which means Moderate. This value is inadequate to minimum requirements of reliability of building safety system that has value of 80 or Good. This is due to safety tools component’s variable that has value of 58,57. It is recommended for the Museum Penerangan management to increase or develop the safety tools’ components that have been lacking of function so that the building could have a better reliability level of potential fire hazard.